Elafin is related to immune infiltration and could predict the poor prognosis in ovarian cancer - Lu, Weiyu; Xie, Biao; Tan, Guangqing; Dai, Wanying; Ren, Jingyi; Pervaz, Sadaf; Li, Kun; Li, Fangfang; Wang, Yingxiong; Wang, Meijiao (Frontiers in Endocrinology, 2023)
Background: Ovarian cancer (OC) is the most lethal gynecologic malignancy, yet clinical results for OC patients are still variable. Therefore, we examined how the elafin expression affects patients’ prognoses and immunotherapy response in OC, which may facilitate treatment selection and improve prognosis. Methods: The elafin mRNA expression profile was downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). Elafin’s prognostic potential and its relationship with clinical variables were investigated using Kaplan-Meier (KM) survival curves, time-dependent receiver operating characteristic (ROC) curves as well as univariate and multivariate Cox regression models. As a validation, the protein expression in tumor and adjacent tissues of OC patients was investigated by using immunohistochemistry (IHC). Comprehensive analyses were then conducted to explore the correlation between immune infiltration and elafin expression. Results: Higher elafin mRNA expression was associated with an unfavorable prognosis in the TCGA cohort and was validated in GSE31245 and IHC. Besides, elafin was indicated as an independent risk factor for OC. Significantly higher protein expression of elafin was detected in adjacent tissues of OC patients with shorter overall survival (OS). The immune-related pathways were mainly enriched in the high elafin mRNA expression group. However, the mRNA expression of elafin was favorably correlated with indicators of immune filtration and immunotherapy response, which also proved better immunotherapy outcomes. Conclusion: The high elafin expression was associated with an unfavorable OS, while it also indicated better immunotherapy responses. Thus, the detection of elafin is beneficial to diagnosis and treatment selection.